Multi-Omics Analysis Reveals a Dependent Relationship Between Rumen Bacteria and Diet of Grass- and Grain-Fed Yaks - Xu, Chenchen; Liu, Wenwen; Sun, Baozhong; Zhang, Songshan; Zhang, Shou; Yang, Yuanli; Lei, Yuanhua; Chang, Lan; Xie, Peng; Suo, Huayi (Frontiers in Microbiology, 2021)
Current information on the differences between rumen bacteria and metabolites of the grass-fed and grain-fed yaks is limited. Understanding the composition and alterations of rumen microbial metabolites is important to clarify its potential role in grass-fed and grain-fed systems. The purpose of this research was to investigate the effects of different production systems on the functional attributes and metabolites in the rumen microbiota of yak using genomics (Illumina MiSeq sequencing of the 16S rRNA gene) and untargeted metabolomics (UHPLC-QTOF-MS). Rumen samples were obtained from grass-fed (C), grain-fed for 3-month (G3), and grain-fed for 6-month yaks (G6). Results showed that the grain-fed yaks presented a lower rumen bacterial richness and diversity when compared to grass-fed yaks. Bacteroidetes, Firmicutes, and Fibrobacteres were the main bacterial phyla. At the phylum and genus level, the grass-fed yaks significantly increased the abundance of Fibrobacteres and Fibrobacter (P<0.05), respectively. The metabolomics analysis revealed that the metabolite profiles differed among the three groups. Compared with the grass-fed group, grain feeding significantly increased azelaic acid, hypoxanthine, uridine, L-phenylalanine, anserine, and decreased alpha-linolenic acid, adenine. Pathway enrichment analysis showed significant differences in metabolic pathways among all comparison groups, but the glycerophospholipid metabolism and alpha-linolenic acid metabolism pathway were common key metabolic pathways. This study showed that the combined analysis of microbiota and metabolites could distinguish different production systems and the fattening time of yaks, providing novel insights for us to understand the function of the rumen bacteria.